Comorbid presentation of syringomyelia and Guillain-Barre syndrome, attributed to mycoplasma, in a 6-year-old female patient. (27th September 2018) - Vampertzi, Olga; Dalpa, Efterpi; Vavilis, Theofanis; Tramma, Despoina
Abstract : Syringomyelia is the development of a fluid-filled cavity or syrinx within the spinal cord that can cause loss of sensation and muscle spasticity. Guillain-Barre syndrome (GBS) is a postinfection autoimmune disease, classified as an acute polyneuropathy. This report describes the emergency admission of a 6-year-old girl presenting with sudden pallor and pain in both lower limbs. The patient's reflexes were normal, as were the results of her sonography, radiography and biochemical tests; however, spinal MRI revealed extensive compartmentalised syringomyelia extending from C2 to T3. A sensory and motor nerve conduction study revealed a demyelinating type motor polyneuropathy which, along with positive Mycoplasma pneumoniae test, was suggestive of GBS. Intravenous immunoglobulin infusion showed excellent results. In conclusion, we report a rare paediatric case of syringomyelia coexisting with GBS. It is important to bear in mind the possibility of other coexisting diseases even if MRI reveals definitive characteristics of another condition.